Karakteristik ekologi, kondisi kesehatan dan tingkat kerawanan degradasi mangrove saat penginisiasian KKPD Rupat Utara 2018 - Syahrial Syahrial; Riri Ezraneti; Bintal Amin; Nur Safira; Dodi Fan Halen Siregar (Dinamika Lingkungan Indonesia, 2021)
The study of ecological characteristics, health conditions and the level of vulnerability of mangrove degradation when initiating North Rupat as a Regional Aquatic Conservation Area (KKPD) was conducted in July 2018 with the aim of future baseline data and comparison. Data collection on the condition of mangrove vegetation is carried out by making line transects and plots drawn from the reference point (outermost mangrove stands) in a direction perpendicular to the coastline to the mainland. The results of the study showed that 12 identified species. The diversity index and dominance are relatively low (H’ ≤ 2.0 and 0 < C ≤ 0.5), while the uniformity is classified as stable (0.75 < E ≤ 1). For the density of mangroves the highest category of trees is at Station 4 (2525 ind/ha ± 638.15), while the density of saplings and seedlings at Station 1 (2800 ind/ha ± 873.48 and 50000 ind/ha ± 17638.34), where Xylocarpus granatum is the dominant species in the tree and seedling category (Importance Value Index/IVI 191.74% and 240.80%), while Avicennia alba was for the saplings category (IVI 216.01%). In the main land part of the North Rupat KKPD area, the mangroves' health condition was increasingly threatened by destruction compared to the small islands around it. However, overall the level of vulnerability of mangrove degradation in the initiating area of North Rupat KKPD is still relatively low.